High-capacity compact hard carbon negative electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202310748829.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-06-25
AI Technical Summary
[0006]为了克服现有技术中的技术问题,本发明提供一种高容量致密型硬碳负极材料及其制备方法与应用,有效解决硬碳嵌钠过程中的可逆容量低、导电性差和结构脆性问题
[0041](1) The high-capacity dense hard carbon anode material disclosed in this invention can effectively solve the problems of low reversible capacity, poor conductivity, and structural brittleness in the sodium intercalation process of hard carbon. Specifically, it is manifested in setting closed pores to increase sodium storage sites, coating the outer carbon layer to reduce the specific surface area of the material, thereby improving the first efficiency and thus increasing the capacity, and occupying irreversible sites through pre-sodiumization to ensure higher reversible capacity. The electron migration efficiency is improved by doping heteroatoms, especially N and P doping, while the external amorphous carbon coating further improves conductivity. The expansion problem in the sodium intercalation process is reduced by setting closed pores and mesopores, reducing the absolute expansion rate and solving the brittleness problem. On the other hand, the external carbon coating has a certain compressive strength.
Smart Images

Figure CN116722139B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sodium-ion battery material technology, and particularly relates to a high-capacity dense hard carbon anode material, its preparation method and application. Background Technology
[0002] With the gradual implementation of dual-carbon policies, the development of sustainable energy storage systems has become crucial for the development of the new energy industry. Sodium-ion batteries, as a novel energy storage device, possess advantages such as low cost, high safety, and abundant resources, making them a key component of energy storage solutions. However, their low energy density and poor cycle stability have become technological bottlenecks limiting the large-scale application of sodium batteries. Therefore, developing high-capacity, high-cycle-performance positive and negative electrode materials is a key strategy for improving the performance of sodium batteries.
[0003] Hard carbon anode materials, due to their unique disordered SP3 hybrid structure, offer high capacity and structural stability, and are considered the most commercially promising anode material for sodium-ion batteries. However, hard carbon suffers from poor conductivity, structural brittleness, and high yield and cost during application, leading to low capacity, poor cycle performance, and high cost in sodium-ion batteries, thus hindering their industrialization.
[0004] To address the aforementioned application issues, relevant research has focused on three aspects: carbon source selection, material structure control, and doping modification. Patent document CN114702022A discloses a method for preparing and applying a hard carbon anode material. This material uses starch as a raw material and obtains a porous hard carbon anode material through four sintering processes. The material exhibits a reversible capacity of 336 mAh / g and an initial coulombic efficiency of 88%, demonstrating high capacity and efficiency. However, this patent uses starch as a carbon source, resulting in low yield and excessively high energy consumption and complex, complex processes, leading to high costs—a key application problem. Patent document CN114141986A discloses an anode material, preparation method, and sodium-ion battery. By constructing a core-shell structure, a double-layer carbon-coated hard carbon anode material is prepared by physically grinding and mixing biomass materials and then carbonizing it. This material has a capacity of 360mAh / g, an initial efficiency of 93%, and a 1C / 1C cycle life of more than 2000 cycles. However, the low yield and unstable source of biomass materials are not conducive to the large-scale industrialization of hard carbon anode materials.
[0005] Therefore, developing a high-capacity, dense, and low-cost hard carbon anode material is crucial for the large-scale application of anodes. Summary of the Invention
[0006] To overcome the technical problems in the prior art, the present invention provides a high-capacity dense hard carbon anode material, its preparation method and application, which effectively solves the problems of low reversible capacity, poor conductivity and structural brittleness in the hard carbon sodium intercalation process.
[0007] To solve the above-mentioned technical problems, the present invention proposes the following technical solution:
[0008] The first aspect of the present invention provides a high-capacity dense hard carbon anode material, wherein the hard carbon anode material has a core-shell structure, comprising a core and a shell covering the outside of the core.
[0009] The core is composed of hard carbon with ordered stacking of carbon microcrystals. The core contains a uniform mesoporous structure and a uniform closed-pore structure inside the core. The closed-pore structure is an incomplete closed pore containing gaps.
[0010] The shell is composed of randomly arranged soft carbon, and the shell is a dense carbon coating layer.
[0011] The hard carbon anode material in this invention has a core-shell structure. The ordered stacking of carbon microcrystals within the core enhances effective sodium storage sites and reduces irreversible capacity. The core contains a closed-pore structure, providing stable insertion sites for sodium ions. This closed-pore structure is not fully closed but contains gaps, facilitating the entry and exit of sodium ions and providing structural stability during rapid sodium insertion / extraction. The core also contains a uniform mesoporous structure, providing both sodium storage sites and expansion space for sodium insertion.
[0012] The shell is a dense carbon coating layer, which on the one hand reduces the specific surface area of the material to ensure the stable formation of the SEI film, and on the other hand enhances the electron migration efficiency of the hard carbon anode material particles and improves conductivity. At the same time, it can also prevent the electrolyte from entering the internal structure of the hard carbon, avoiding the continuous erosion of the particles by the electrolyte during the sodium insertion / extraction process, which would lead to a decrease in cycle performance.
[0013] As an optional implementation, in the hard carbon anode material provided by the present invention, the spacing between the hard carbon layers inside the core is 0.37 to 0.45 nm, the size of the closed-pore structure is 2 to 50 nm, and the thickness of the coated carbon layer is 1 to 50 nm.
[0014] Controlling the interlayer spacing to 0.37–0.45 nm can effectively increase the number of sodium insertions and extractions in the carbon microcrystalline structure. Closed-pore structures can increase sodium storage sites, allowing for greater sodium storage capacity. A carbon coating thickness in the range of 1–50 nm can improve the stability of the particulate material.
[0015] As an optional implementation, in the hard carbon anode material provided by the present invention, the core contains a doping element, which is selected from one or more of nitrogen, phosphorus, and boron.
[0016] Doping the core with nitrogen, phosphorus, or boron can improve the electron mobility of hard carbon anode materials.
[0017] As an optional implementation, in the hard carbon anode material provided by the present invention, the carbon content accounts for 80-99% by mass, the oxygen content accounts for 0.01-8% by mass, the doping element content accounts for 0.01-5% by mass, the Na content accounts for 0.01-2% by mass, and the content of other impurities is <50ppm.
[0018] The hard carbon anode material of this invention has a low oxygen content by mass, ranging from 0.01% to 8%, indicating that the anode material particles contain fewer hydroxyl and carboxyl groups. This avoids problems such as "a high content of hydroxyl and carboxyl groups in the anode material easily leads to the formation of byproducts (water, CO2, etc.) during sodium intercalation, which on the one hand reduces reversible capacity and on the other hand causes gas generation in the battery."
[0019] As an optional implementation, in the hard carbon anode material provided by the present invention, the hard carbon anode material is spherical with a D50 of 3–10 μm and a tap density of 0.8–1.2 g / cm³. 3 Specific surface area ≤ 5m² 2 / g.
[0020] Based on the same technical concept, a second aspect of the present invention also provides a method for preparing a high-capacity dense hard carbon anode material, comprising the following steps:
[0021] S1. Disperse the carbon source, dopant, and pre-sodium agent in a solvent to form dispersion A, wherein the carbon source includes a first carbon source and a second carbon source.
[0022] S2. Dispersion A is injected into a curing and drying device for granulation and curing to obtain particles B. The curing and drying temperature is 50-200℃.
[0023] S3. Place particle B in a low-temperature carbonization furnace for staged heating, and obtain powder C through low-temperature carbonization decomposition.
[0024] S4. Place the powder C in a high-temperature coating furnace, introduce an organic gas source, and obtain a high-capacity dense hard carbon anode material through high-temperature coating.
[0025] In this invention, heterocyclic and non-heterocyclic organic carbon sources, dopants, and pre-sodium agents are first uniformly dispersed and then granulated after curing and drying. The temperature during granulation is controlled at 50–200°C. The heterocyclic organic carbon source undergoes cross-linking, forming closed-cell structures with a near-closed structure during curing and drying. Then, particles B are subjected to low-temperature carbonization. During carbonization, organic matter decomposes, carbon atoms rearrange, and a hard carbon structure with ordered stacking of carbon microcrystals is formed. The through-pore structure formed by the overflow of gases such as hydrogen, CO2, and water vapor generated during carbonization is mesopores. Simultaneously, the carbonization process involves a certain temperature, further forming closed pores in the material. Finally, a high-temperature coating is applied to obtain a shell composed of randomly arranged soft carbon. The resulting carbon coating reduces the specific surface area of the material and enhances its electrical conductivity.
[0026] As an optional implementation, in the hard carbon anode material provided by the present invention, the first carbon source is selected from one or more of cellulose, lignin, furfural, furan resin, phenolic resin, resorcinol formaldehyde resin, and urea-formaldehyde resin, and the second carbon source is selected from one or more of graphite powder, xylose, polyvinylpyrrolidone, polyacrylamide, polyethylene, polypropylene, and polyphenylene sulfide.
[0027] As an optional implementation, in the hard carbon anode material provided by the present invention, the dopant is selected from one or more of melamine, ammonium nitrate, boric acid, sodium borohydride, hydrazine hydrate, ammonium bicarbonate, urea, ammonium dihydrogen phosphate, and ammonium hydrogen phosphate.
[0028] As an optional implementation, in the hard carbon anode material provided by the present invention, the pre-sodium agent is selected from one of sodium carbonate, sodium bicarbonate, sodium phosphate, sodium hydrogen phosphate, sodium sulfate, sodium sulfite, sodium acetate, sodium sulfonate, and sodium carboxymethyl cellulose.
[0029] As an optional implementation, in the hard carbon anode material provided by the present invention, the molar ratio of the carbon source, dopant and pre-sodium agent is (10-100):(0.001-0.1):(0.001-0.1).
[0030] As an optional implementation, in the hard carbon anode material provided by the present invention, in step S2, the inlet temperature of the curing and drying equipment is 100-200°C and the outlet temperature is 50-100°C.
[0031] As an optional implementation, in the hard carbon anode material provided by the present invention, in step S3, the low-temperature carbonization temperature is 300-600℃, the carbonization time is 1-10h, and the heating rate is 0.5-5℃ / min.
[0032] In this invention, low-temperature carbonization is first carried out at 300-600°C. During the carbonization process, gases such as hydrogen, CO2, and water vapor are released to form a mesoporous structure, while the closed pores in the material undergo further changes.
[0033] Furthermore, in the low-temperature carbonization process, the temperature is first increased to 300-400℃ at a rate of 1-2℃ / min and held for 3-4 hours, and then increased to 500-600℃ at a rate of 1-5℃ / min and held for 2 hours.
[0034] In this invention, during the low-temperature carbonization process, the heating rate in the first stage is slow, so that the gas overflow rate is slow and the mesopore size is small; the heating rate in the second stage is accelerated, so that the carbon source carbonization speed is accelerated, further promoting a larger carbon layer spacing.
[0035] As an optional implementation, in the hard carbon anode material provided by the present invention, in step S3, the low-temperature carbonization furnace is selected from one of the following: a stirred reactor, a VCJ carbonization furnace, a rotary carbonization furnace, and a microwave fluidized bed carbonization furnace.
[0036] As an optional implementation, in the hard carbon anode material provided by the present invention, in step S4, the high-temperature coating temperature is 800-1400°C, the coating time is 1-6h, and the heating rate is 2-10°C / min.
[0037] As an optional implementation, in the hard carbon anode material provided by the present invention, in step S4, the high-temperature coating furnace is selected from one of the following: vapor deposition furnace, rotary kiln, microwave vapor deposition furnace, and vapor fluidized bed.
[0038] As an optional implementation, in the hard carbon anode material provided by the present invention, in step S2, the curing and drying equipment is selected from one of the following: fluidized bed dryer, centrifugal spray dryer, pressure spray dryer, flexible spray dryer, liquid phase atomization dryer, and wet coating dryer.
[0039] As an optional implementation, in the hard carbon anode material provided by the present invention, in step S4, the organic carbon source is selected from one or more of methane, ethylene, acetylene, propylene, propane, butadiene, and toluene, and the carrier gas is 5% by volume of nitrogen-hydrogen or argon-hydrogen; the molar ratio of organic gas source to carrier gas is 1:(1-100).
[0040] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0041] (1) The high-capacity dense hard carbon anode material disclosed in this invention can effectively solve the problems of low reversible capacity, poor conductivity, and structural brittleness in the sodium intercalation process of hard carbon. Specifically, it is manifested in setting closed pores to increase sodium storage sites, coating the outer carbon layer to reduce the specific surface area of the material, thereby improving the first efficiency and thus increasing the capacity, and occupying irreversible sites through pre-sodiumization to ensure higher reversible capacity. The electron migration efficiency is improved by doping heteroatoms, especially N and P doping, while the external amorphous carbon coating further improves conductivity. The expansion problem in the sodium intercalation process is reduced by setting closed pores and mesopores, reducing the absolute expansion rate and solving the brittleness problem. On the other hand, the external carbon coating has a certain compressive strength.
[0042] (2) In the hard carbon anode material of the present invention, the outer shell is a stable soft carbon structure, which is not only conducive to the effective transport of electrons and sodium ions, but also can isolate the intrusion of electrolyte, ensure the stable formation of SEI during the rapid deintercalation and deintercalation of hard carbon, and improve the cycle performance of the material. Attached Figure Description
[0043] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0044] Figure 1 This is a schematic diagram of the structure of the hard carbon anode material prepared in this invention;
[0045] Figure 2 This is a SEM image of the hard carbon anode material prepared in Example 3 of the present invention;
[0046] Figure 3 This is a TEM image of the hard carbon anode material prepared in Example 3 of the present invention;
[0047] Figure 4 This is a SEM image of the hard carbon anode material prepared in Comparative Example 3 of this invention.
[0048] Figure 5 This is a closed-pore TEM image of the hard carbon anode material prepared in Comparative Example 5 of the present invention. Detailed Implementation
[0049] To facilitate understanding of the present invention, the present invention will be described more fully and in detail below with reference to the accompanying drawings and preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.
[0050] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0051] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0052] Example 1:
[0053] (1) Weigh 2kg of cellulose powder and 100g of sodium sulfite and grind them in a ball mill at 500rpm for 30min and disperse them in 5L of aqueous solution. Add 0.5kg of graphite powder with D50 of 3μm and 100g of urea to the solution and disperse for 30min to form a uniform dispersion.
[0054] (2) 7 kg of dispersion was pumped into a pressure spray dryer using a peristaltic pump. The nozzle pressure was adjusted to 0.5 MPa, the inlet temperature was adjusted to 160°C, and the outlet temperature was adjusted to 100°C. After atomization, the powder was formed and collected in a cyclone separator with a material D50 of 5 μm.
[0055] (3) Take 1 kg of powder and place it in the VCJ sintering furnace. First, heat it to 300℃ at 1℃ / min and keep it at 4h. Then, heat it to 500℃ at 2℃ / min and keep it at 2h. After cooling to room temperature, discharge the material to form carbonized material.
[0056] (4) Place 200g of cooling material in a rotary sintering furnace, introduce a mixture of acetylene and methane with a molar ratio of 1 / 3, heat up at a rate of 5℃ / min until the deposition temperature is 900℃, deposit for 6h, the flow rate of the mixed gas is 5L / min, the flow rate of hydrogen in argon with 5% carrier gas is 13L / min; after deposition, a hard carbon anode material with a D50 of 6μm is obtained.
[0057] Example 2
[0058] (1) Weigh 2kg of lignin, 100g of sodium bicarbonate and 100g of ammonium hydrogen phosphate and grind them in a vertical mixer at 1000rpm for 1h and disperse them in 5L of aqueous solution. Add 0.5kg of xylose to the solution and disperse for 30min to form a uniform dispersion.
[0059] (2) 7 kg of dispersion was pumped into a centrifugal spray dryer using a hydraulic pump. The speed of the centrifugal atomizing disc was adjusted to 20,000 rpm, the inlet temperature was adjusted to 170°C, and the outlet temperature was adjusted to 110°C. After atomization, powder was formed and collected in a cyclone separator with a material D50 of 8 μm.
[0060] (3) Take 1 kg of powder and place it in a stirred reactor. Stir at 15 rpm, heat to 400℃ at 2℃ / min and keep for 3 hours, then heat to 600℃ at 5℃ / min and keep for 2 hours. After cooling to room temperature, discharge the material to form carbonized material.
[0061] (4) Place 200g of cooling material in a microwave vapor deposition furnace, introduce a mixed gas of ethylene and methane with a molar ratio of 1 / 2, heat up at a rate of 5℃ / min until the deposition temperature is 1100℃, deposit for 4h, the flow rate of the mixed gas is 2L / min, the flow rate of hydrogen in the carrier gas is 5% nitrogen and 5L / min; after deposition, a hard carbon material with a D50 of 9μm is obtained.
[0062] Example 3
[0063] (1) Weigh 3kg of urea-formaldehyde resin, 100g of melamine and 100g of sodium sulfate and disperse them in 5L of ethanol at 1000rpm for 20min using a homogenizer. Then add 0.5kg of polyvinylpyrrolidone to the solution and disperse for 30min to form a uniform dispersion.
[0064] (2) 7 kg of dispersion was pumped into a fluidized bed dryer using a mechanical pump. The pressure of the atomizing nozzle was adjusted to 5 MPa, the inlet temperature was adjusted to 130℃, the outlet temperature was adjusted to 80℃, and the bed pressure drop was controlled to 0.3 MPa. After drying, the material D50 was collected in a cyclone separator and found to be 13 μm.
[0065] (3) Take 1 kg of powder and place it in a stirred reactor. Stir at 15 rpm, heat to 400℃ at 2℃ / min and keep for 3 hours, then heat to 600℃ at 5℃ / min and keep for 2 hours. After cooling to room temperature, discharge the material to form carbonized material.
[0066] (4) Place 200g of cooling material in a microwave vapor deposition furnace, introduce a mixed gas of propylene and toluene with a molar ratio of 1 / 4, heat up at a rate of 5℃ / min until the deposition temperature is 1400℃, deposit for 2h, the flow rate of the mixed gas is 5L / min, the flow rate of hydrogen in the carrier gas is 10L / min in nitrogen of 5%; after deposition, a hard carbon material with a D50 of 15μm is obtained.
[0067] SEM images of hard carbon anode materials are shown below. Figure 2 As shown.
[0068] Example 4
[0069] (1) Weigh 4kg of phenolic resin, 100g of boric acid and 100g of sodium carbonate and disperse them in 5L of ethanol at 1500rpm for 10min using a dual planetary machine. Then add 0.5kg of polyacrylamide to the solution and disperse it into a uniform dispersion for 20min.
[0070] (2) 7 kg of dispersion was pumped into a fluidized bed dryer using a mechanical pump. The pressure of the atomizing nozzle was adjusted to 8 MPa, the inlet temperature was adjusted to 150℃, the outlet temperature was adjusted to 70℃, and the bed pressure drop was controlled to 0.4 MPa. After drying, the material D50 was collected in a cyclone separator and found to be 5 μm.
[0071] (3) Take 1 kg of powder and place it in a stirred reactor. Stir at 15 rpm, heat to 300℃ at 1℃ / min and keep for 3 hours. Then heat to 800℃ at 1℃ / min and keep for 2 hours. After cooling to room temperature, discharge the material to form carbonized material.
[0072] (4) Place 200g of cooling material in a microwave vapor deposition furnace, introduce a mixture of methane and toluene with a molar ratio of 1 / 6, heat up at a rate of 5℃ / min until the deposition temperature is 1400℃, deposit for 2h, the flow rate of the mixed gas is 5L / min, the flow rate of hydrogen in the carrier gas is 10L / min in nitrogen of 5%; after deposition, a hard carbon material with a D50 of 7μm is obtained.
[0073] Comparative Example 1
[0074] (1) Weigh 2kg of cellulose powder and 100g of sodium sulfite and grind them in a ball mill at 500rpm for 30min and disperse them in 5L of aqueous solution. Add 0.5kg of graphite powder with D50 of 3μm and 100g of urea to the solution and disperse for 30min to form a uniform dispersion.
[0075] (2) The dispersion was dried in a vacuum oven at 100°C for 24 hours, then formed into lumps and crushed in a universal pulverizer at 3000 rpm for 30 minutes to obtain powder.
[0076] (3) Take 1 kg of powder and place it in the VCJ sintering furnace. First, heat it to 300℃ at 1℃ / min and keep it at 4h. Then, heat it to 500℃ at 2℃ / min and keep it at 2h. After cooling to room temperature, discharge the material to form carbonized material.
[0077] (4) Place 200g of cooling material in a rotary sintering furnace, introduce a mixture of acetylene and methane with a molar ratio of 1 / 3, heat up at a rate of 5℃ / min until the deposition temperature is 900℃, deposit for 6h, the flow rate of the mixed gas is 5L / min, the flow rate of hydrogen in argon with 5% carrier gas is 13L / min; after deposition, a hard carbon anode material with a D50 of 6μm is obtained.
[0078] Comparative Example 2
[0079] (1) Weigh 2kg of cellulose powder and 100g of sodium sulfite, grind them in a ball mill at 500rpm for 30min and disperse them in 5L of aqueous solution. Add 0.5kg of xylose to the solution and disperse at 2000rpm for 30min to form a uniform dispersion.
[0080] (2) 7 kg of dispersion was pumped into a centrifugal spray dryer using a hydraulic pump. The speed of the centrifugal atomizing disc was adjusted to 20,000 rpm, the inlet temperature was adjusted to 170°C, and the outlet temperature was adjusted to 110°C. After atomization, powder was formed and collected in a cyclone separator with a material D50 of 8 μm.
[0081] (3) Take 1 kg of powder and place it in a stirred reactor. Stir at 15 rpm, heat to 400℃ at 2℃ / min and keep for 3 hours, then heat to 600℃ at 5℃ / min and keep for 2 hours. After cooling to room temperature, discharge the material to form carbonized material.
[0082] (4) Place 200g of cooling material in a microwave vapor deposition furnace, introduce a mixed gas of ethylene and methane with a molar ratio of 1 / 2, heat up at a rate of 5℃ / min until the deposition temperature is 1100℃, deposit for 4h, the flow rate of the mixed gas is 2L / min, the flow rate of hydrogen in the carrier gas is 5% nitrogen and 5L / min; after deposition, a hard carbon material with a D50 of 9μm is obtained.
[0083] Comparative Example 3
[0084] (1) Weigh 3kg of urea-formaldehyde resin and 100g of melamine and disperse them in 5L of ethanol at 1000rpm for 20min using a homogenizer. Then add 0.5kg of polyvinylpyrrolidone to the solution and disperse for 30min to form a uniform dispersion.
[0085] (2) 7 kg of dispersion was pumped into a fluidized bed dryer using a mechanical pump. The pressure of the atomizing nozzle was adjusted to 5 MPa, the inlet temperature was adjusted to 130℃, the outlet temperature was adjusted to 80℃, and the bed pressure drop was controlled to 0.3 MPa. After drying, the material D50 was collected in a cyclone separator and found to be 13 μm.
[0086] (3) Take 1 kg of powder and place it in a stirred reactor. Stir at 15 rpm, heat to 400℃ at 2℃ / min and keep for 3 hours, then heat to 600℃ at 5℃ / min and keep for 2 hours. After cooling to room temperature, discharge the material to form carbonized material.
[0087] (4) Place 200g of cooling material in a microwave vapor deposition furnace, introduce a mixed gas of propylene and toluene with a molar ratio of 1 / 4, heat up at a rate of 5℃ / min until the deposition temperature is 1400℃, deposit for 2h, the flow rate of the mixed gas is 5L / min, the flow rate of hydrogen in the carrier gas is 10L / min in nitrogen of 5%; after deposition, a hard carbon material with a D50 of 15μm is obtained.
[0088] Comparative Example 4
[0089] (1) Weigh 3kg of urea-formaldehyde resin, 100g of melamine and 100g of sodium sulfate and disperse them in 5L of ethanol at 1000rpm for 20min using a homogenizer. Then add 0.5kg of polyvinylpyrrolidone to the solution and disperse for 30min to form a uniform dispersion.
[0090] (2) The dispersion was dried in a vacuum oven at 100°C for 24 hours and then formed into blocks. The blocks were crushed in a universal crusher at 10,000 rpm for 10 minutes and passed through a 325-mesh sieve to obtain crushed material with a D50 of 15 μm.
[0091] (3) Take 1 kg and place it in a box furnace. Purge nitrogen gas and heat to 800℃ at 5℃ / min. Hold for 2 hours. After cooling to room temperature, discharge the material to form carbonized blocks with a D50 of 16µm.
[0092] Comparative Example 5
[0093] (1) Weigh 3 kg of urea-formaldehyde resin and disperse it in 5 L of ethanol at 1000 rpm for 20 min using a homogenizer. Then add 0.5 kg of polyvinylpyrrolidone to the solution and disperse it into a uniform dispersion for 30 min.
[0094] (2) 7 kg of dispersion was pumped into a fluidized bed dryer using a mechanical pump. The pressure of the atomizing nozzle was adjusted to 5 MPa, the inlet temperature was adjusted to 130℃, the outlet temperature was adjusted to 80℃, and the bed pressure drop was controlled to 0.3 MPa. After drying, the material D50 was collected in a cyclone separator and found to be 13 μm.
[0095] (3) Take 1 kg of powder and place it in a stirred reactor. Stir at 15 rpm, heat to 400℃ at 2℃ / min and keep for 3 hours, then heat to 600℃ at 5℃ / min and keep for 2 hours. After cooling to room temperature, discharge the material to form carbonized material with a D50 of 14 μm.
[0096] Product performance testing
[0097] The silicon-based anode materials prepared in Examples 1-4 of this invention include a hard carbon anode material with a core-shell structure, comprising a core 1 and a shell 2 covering the core 1. The core is composed of hard carbon composed of ordered stacked carbon microcrystals, and contains a uniform closed-pore structure 3 with gaps to facilitate the entry and exit of sodium. The shell is a dense carbon coating layer. A schematic diagram of its structure is shown below. Figure 1 As shown.
[0098] The morphological characteristics of the negative electrode material prepared in Example 3 are as follows: Figure 2 As shown, from Figure 2 The prepared hard carbon anode material is granular with a particle size (D50) of approximately 13 μm. SEM analysis reveals a smooth outer coating on the particles, and the absence of pores on the particle surface indicates a tight coating. TEM characterization of the particles yielded the following results: Figure 3 As shown, the results indicate that hard carbon exhibits a distinct core-shell structure, with the shell coated with a relatively uniform carbon layer of approximately 30 nm thickness. The core consists of a hard carbon structure formed by stacked carbon microcrystals. This structure can be derived from… Figure 5 The discontinuous layered microcrystalline structure was derived.
[0099] In the hard carbon anode material of this invention, the closed-pore diameter is approximately 2–5 nm, such as… Figure 5 As shown, the cross-section of the particle reveals that the nucleus contains a uniform closed-pore structure. The closed-pore structure is an incomplete closed pore containing gaps, and the circled part in the figure represents the closed pore.
[0100] The hard carbon anode material prepared in Comparative Example 4, such as Figure 4 As shown, the blocky phenomenon is obvious, and the particles have obvious edges or points, which can easily cause point discharge during charging and discharging, resulting in voltage lag.
[0101] The characterization parameters of the negative electrode materials prepared in Examples 1-4 and Comparative Examples 1-5 are shown in Table 1 below.
[0102] Table 1: Characterization parameters of negative electrode materials
[0103]
[0104] Table 1 shows that Examples 1-4 have incorporated N, B, or P into the hard carbon anode material matrix. In contrast, Comparative Example 2, which did not incorporate N, B, or P, does not show this. In Examples 1-4, carbon content is dominant, accounting for approximately 80-93%, with lower oxygen content. Furthermore, the impurity content in these examples can be controlled below 30 ppm, while Comparative Example 2 has a higher oxygen content. Additionally, the hard carbon layer structure in each example can be well controlled between 0.37-0.43 nm. Comparative Example 1 is a hard carbon material without a closed-cell structure. Compared to Example 1, Comparative Example 1 has fewer sodium storage sites, resulting in a lower sodium content. Comparative Example 3 did not undergo pre-sodium incorporation, and its sodium content is 0. Comparing the comparative examples with the examples, a significant decrease in mesopore volume is evident in Examples 1-4, indicating less exposed mesopores and a better coating effect.
[0105] The present invention employs the following method to test the performance of the hard carbon anode precursor materials of Examples 1-4 and Comparative Examples 1-5. The hard carbon anode material (CMC:SBR = 7:2:1) is slurried, with the solid content of the slurry controlled at 55%. This slurry is then coated onto an aluminum foil current collector to obtain the anode sheet. The compacted density of the electrode sheet is controlled at 1.4-1.6 g / cm³. 3 A 2032 coin cell was constructed using a sodium metal sheet as the counter electrode, and its capacity and initial efficiency were tested. An 18650 battery was fabricated using a commercially available ternary layered oxide as the positive electrode and subjected to cycle testing.
[0106] The physicochemical properties of the anode materials prepared in Examples 1-4 and Comparative Examples 1-5 are shown in Table 2 below.
[0107] Table 2: Physicochemical Performance Parameters of Anode Materials
[0108]
[0109] As shown in Table 2, the tap density of the hard carbon anodes in Examples 1-4 has been significantly improved, reaching 0.9-1.2 g / cm³. 3 Horizontal, and the specific surface area can be controlled within 5m² 2 Below / g, it meets commercial requirements. A comparison of Example 1 and Comparative Example 1 shows that the closed-cell structure significantly improves the sodium intercalation capacity of hard carbon materials and exhibits superior cycle performance, outperforming hard carbon anode materials formed through carbonization-crushing in the industry. A comparison of Example 2 and Comparative Example 2 shows that heteroatom doping can also improve the material's capacity and first-efficiency, while simultaneously enhancing structural stability to ensure better cycle performance. A comparison of Example 3 and Comparative Example 3 shows that pre-sodiumization reduces irreversible sites, improves capacity and first-efficiency, and ensures superior cycle performance. A comparison of Example 4 and Comparative Example 5 shows that external coating significantly reduces the material's specific surface area, thereby achieving stable SEI film formation and ensuring superior cycle performance.
[0110] The above description, in conjunction with specific preferred embodiments, provides a further detailed explanation of the present invention. It should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, various simple deductions or substitutions can be made without departing from the concept of the present invention, and all such modifications and substitutions should be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a high-capacity, dense hard carbon anode material, characterized in that, Includes the following steps: S1. Disperse the carbon source, dopant, and pre-sodium agent in a solvent to form dispersion A. The carbon source includes a first carbon source and a second carbon source. The first carbon source is selected from one or more of cellulose, lignin, furfural, furan resin, phenolic resin, resorcinol-formaldehyde resin, and urea-formaldehyde resin. The second carbon source is selected from one or more of graphite powder, xylose, polyvinylpyrrolidone, polyacrylamide, polyethylene, polypropylene, and polyphenylene sulfide. S2. Dispersion A is injected into a curing and drying equipment for granulation and curing to obtain particles B. The curing and drying temperature is 50~200℃. The curing and drying equipment is selected from one of the following: fluidized bed dryer, centrifugal spray dryer, pressure spray dryer, flexible spray dryer, liquid phase atomizing dryer, and wet coating dryer. S3. Place particle B in a low-temperature carbonization furnace for staged heating. After low-temperature carbonization and decomposition, obtain powder C. The low-temperature carbonization process first heats up to 300-400℃ at 1-2℃ / min and holds for 3-4 hours, then heats up to 500-600℃ at 1-5℃ / min and holds for 2 hours. S4. Place powder C in a high-temperature coating furnace, introduce an organic gas source, and obtain a high-capacity dense hard carbon anode material through high-temperature coating. The hard carbon anode material prepared by the above method has a core-shell structure, including a core and a shell covering the outside of the core; the core is composed of hard carbon with ordered stacking of carbon microcrystals, the core contains a uniform mesoporous structure, the core contains a uniform closed-pore structure inside, the closed-pore structure is an incomplete closed pore with gaps; the shell is composed of disordered soft carbon, the shell is a dense carbon coating layer.
2. The method for preparing the high-capacity dense hard carbon anode material according to claim 1, characterized in that, The hard carbon anode material has a hard carbon layer spacing of 0.37~0.45nm inside the core, a closed-pore structure size of 2~50nm, and a carbon coating thickness of 1~50nm.
3. The method for preparing the high-capacity dense hard carbon anode material according to claim 1, characterized in that, The core of the hard carbon anode material contains doping elements, which are selected from one or more of nitrogen, phosphorus, and boron.
4. The method for preparing the high-capacity dense hard carbon anode material according to claim 1, characterized in that, The hard carbon anode material contains 80-99% carbon by mass, 0.01-8% oxygen by mass, 0.01-5% doping elements, 0.01-2% Na by mass, and other impurities <50ppm.
5. The method for preparing the high-capacity dense hard carbon anode material according to claim 1, characterized in that, The hard carbon anode material is spherical with a D50 of 3~10 μm and a tap density of 0.8~1.2 g / cm³. 3 Specific surface area ≤ 5m² 2 / g.
6. The method for preparing high-capacity dense hard carbon anode material according to claim 1, characterized in that, The molar ratio of the carbon source, dopant, and pre-sodium agent is (10-100):(0.001-0.1):(0.001-0.1).
7. The method for preparing the high-capacity dense hard carbon anode material according to claim 1, characterized in that, In step S2, the inlet temperature of the curing and drying equipment is 100~200℃, and the outlet temperature is 50~100℃.
8. The method for preparing high-capacity dense hard carbon anode material according to claim 1, characterized in that, In step S3, the low-temperature carbonization temperature is 300~600℃, the carbonization time is 1~10h, and the heating rate is 0.5~5℃ / min; in step S4, the high-temperature coating temperature is 800~1400℃, the coating time is 1~6h, and the heating rate is 2~10℃ / min.
9. The application of the hard carbon anode material prepared by the preparation method of the high-capacity dense hard carbon anode material according to any one of claims 1-8 in sodium-ion batteries.
Citation Information
Patent Citations
Negative electrode material, preparation method and sodium ion battery
CN114141986A
Preparation method and application of hard carbon negative electrode material
CN114702022A
Composite carbon material and preparation method and application thereof
CN108878774A
Silicon-carbon negative electrode material for lithium ion battery and preparation method of silicon-carbon negative electrode material
CN109873146A
High-rate hard carbon negative electrode material and preparation method and application thereof
CN115849332A